Problem-Based Learning Model on Students' Chemical Literacy and Critical Thinking on Reaction Rate Material - Fareza, Fadhila Shafa; Van Hayus, Elfi Susanti; Ari Syahidul Shidiq; Sri Yamtinah; Mohammad Masykuri; Maria Ulfa; Agung Nugroho Catur Saputro; Bakti Mulyani (Jurnal Pendidikan Indonesia, 2024)
This study was motivated by students'students' low chemical literacy skills and critical thinking skills. One way to overcome this problem is to actively use a learning model involving students, such as problem-based learning (PBL). This research aims to analyze the effect of PBL on students' chemical literacy and critical thinking skills. This study used a quantitative approach with a quasi-experimental method. The research design used was a non-equivalent control group design. The sample selection technique used was cluster random sampling, which was done by selecting 70 second-grade high school students. Data collection using tests with instruments in the form of essay test sheets regarding posttest chemical literacy skills with as many as seven questions and posttest critical thinking skills with as many as five questions. Data analysis techniques using non-parametric statistical tests. Hypothesis testing using the Kruskal-Wallis test. The results showed a significant difference between students taught with the PBL model and students who were not trained with the model. Applying the PBL model is proven to affect students' chemical literacy and critical thinking skills. Thus, it can be concluded that the application of PBL can significantly improve students' chemical literacy and essential thinking skills compared to learning methods that do not use the model. This study implies that problem-based learning models can influence students' chemical literacy and critical thinking skills with implementation tailored to the context and material in this study, namely reaction rates.